PENGEMBANGAN KAWASAN WISATA AIR TERJUN CUNCA REDE DI DESA SANOLOKOM KECAMATAN RANA MESE KABUPATEN MANGGARAI TIMUR - Anut, Fransiska; Samin, Mikael; H. N. Mari, Natalia Adel (Jurnal Geografi, 2021)
The aimed of this study was to determine the internal and external factors supporting and inhibiting the development of the Cunca Rede Waterfall Tourism Area in Sanolokom Village, Rana Mese District, East Manggarai Regency. The method used in this study is a descriptive method with a qualitative approach and the data sources used by the researcher are primary data and secondary data. . The data analysis technique used is SWOT analysis. The results show that based on the Cartesian diagram, the SWOT analysis of tourist attraction in quadrant 1 with the results of the recapitulation between strengths and opportunities has results where the dominant strength is compared to the weakness and the opportunity was greater than the threat with the following values: 1) Strengths - Weaknesses (factors internal) : 4.12-1.88=2.24) Opportunities –Threats (external factors) : 1.84-4.34 = -2.5 and the development strategy of the Cunca Rede Waterfall Tourism Area carried out by the Government was: 1) Empowering, counseling in order to grow and increase public awareness about the importance of a tourism-aware community, 2) Coordinate with the private sector to invest in tourism development problems are strongly influenced by the availability of budget funds to build and manage a tourist attraction, 3) Build and holding tourism accessibility, 4) Developing tourism attractions.